Kvicksilver, kadmium och zink i avfall som förbränns i Kiruna kraftvärmeverk - Andersson, Elin (SLU/Dept. of Soil and Environment, 2016)
Kiruna Kraft AB is the responsible operator of the Kiruna power and heating plant and the Kiruna waste disposal plant. The company is responsible for the production and distribution of heating and electricity in Kiruna and for heat from the heating plant in Vittangi. In addition, the company takes care of household waste from municipality citizens. The company is authorized to incinerate more than 98 000 tons of waste per calendar year with a maximum of 2,500 tons of hazardous waste.